PRAKTIK GOOD GOVERNANCE DALAM PELAYANAN PUBLIK PADA PEMERINTAHAN DESA DI BONTO JAI KECAMATAN BISSAPPU KABUPATEN BANTAENG - Angraeni E, Vivi; Malik, Ihyani; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to find out the good governance practices of the village government of Bonto Jai, Bissappu District, Bantaeng Regency and the inhibiting and supporting factors. This type of research is qualitative research with a descriptive approach to collecting data using observation, interviews, and documentation. Data analysis technique is data reduction, data presentation. Research results Participation in the village of Bonto Jai was built through formulation, implementation and evaluation. Improving community and government services that work together to solve a problem related to public services in Bonto Jai Village. Transparency conveying policy or program information using direct media and social media. Accountability for implementing the accuracy and completeness of information data in the implementation of village policies or programs. Appropriateness of information data submitted to the public. Supporting factors are cooperation and communication while inhibiting factors are human resource competence, lack of discipline and apathy.